Pure optical dynamical color encryption - Mosso Solano, Edward Fabian (2011)
We introduce a way to encrypt-decrypt a color dynamical phenomenon using a pure optical alternative. We split the three basic chromatic channels composing the input, and then each channel is processed through a 4f encoding method and a theta modulation applied to the each encrypted frame in every channel. All frames for a single channel are multiplexed. The same phase mask is used to encode all the information. Unlike the usual procedure we do not multiplex the three chromatic channels into a single encoding media, because we want to decrypt the information in real time. Then, we send to the decoding station the phase mask and the three packages each one containing the multiplexing of a single channel. The end user synchronizes and decodes the information contained in the separate channels. Finally, the decoding information is conveyed together to bring the decoded dynamical color phenomenon in real-time. We present material that supports our concepts.